Penerapan Kurikulum Merdeka melalui Kompetisi Bebras Computational Thinking untuk Siswa Sekolah Dasar - Apriani, Apriani; Ibrahim, Isra Dewi Kuntary; Muhid, Abdul (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Computational thinking is a critical thinking technique that is included in subjects to improve students' thinking skills. Meanwhile, the Kurikulum Merdeka is a policy in the education to make it easier for educational institutions, teachers and even students in the learning process. The presence of Bebras at Sekolah Dasar Negeri 8 Sokong, North Lombok Regency aims to improve teachers' teaching abilities and increase children's creativity to solve problems in subjects. The method used in this program are planning, preparation, socialization and training, and competition and evaluation Stage. The final result obtained was that the teacher was able to apply content to school subjects and sent the students of SDN 8 Sokong to take part in local and national level competitions. The content of Kurikulum Kampus Merdeka can produce competitive output for students are taught by their teachers to think computationally and find quick solutions to the problems given. One form of evaluating Bebras progress towards its students is competitions, both local and national, while the evaluation of the teacher's abilities is seen from the abilities of the students. The collaboration between Bebras Bureau Bumigora University and SDN 8 Sokong enable the students to compete at the national level.